Preparation method and application of carbon-based anode material

By optimizing the ratio of coal powder pretreatment and suspension, an efficient carbon-based anode material was prepared, which solved the problems of complexity and performance limitations of traditional carbon-based materials, and significantly reduced the energy consumption of hydrogen production by electrolyzing water.

CN119571357APending Publication Date: 2025-03-07CHINA DATANG GRP TECH INNOVATION CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411758064.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

Traditional carbon-based materials have preparation complexity and performance limitations in the process of electrolyzing water hydrogen production, resulting in high power consumption and increased system complexity.

Method used

By pretreating the coal powder and mixing it with Nafion solution and ethanol to form a stable suspension, it is uniformly applied on the carbon cloth substrate to form an electrode, and the ratio of the carbon-based anode material and the preparation process are optimized.

Benefits of technology

The uniform fixation of carbon powder is achieved, the specific surface area and electrochemical performance of the anode are improved, the energy consumption of hydrogen production is significantly reduced, and the preparation process is simplified.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119571357A_ABST
    Figure CN119571357A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a carbon-based anode material, and relates to the field of electrolytic hydrogen production. The method comprises the following steps: 1, preparing a carbon powder material; 2, activating the carbon material at high temperature; 3, cleaning and sieving; 4, preparing turbid liquid; and 5, uniformly dispensing the turbid liquid on hydrophilic carbon cloth in batches, and drying to obtain the carbon-based anode material. The utilization rate of the pulverized coal is increased, the solution resistance is reduced, the carbon powder is uniformly fixed on the surface of the anode, and the problem of particle sedimentation is avoided; the specific surface area of the anode is increased; the interface catalytic performance is improved; and the bonding strength between the carbon powder and the electrode material is improved, so that the influence of solution resistance in the electrolysis process is reduced. The method is combined with an iron-based circulation (Fe < 2 + > / Fe < 3 + >) system, the anodic oxidation potential is remarkably reduced, the oxidation kinetics is improved, and the efficiency of hydrogen production through water electrolysis is improved; through iron-based circulation assistance and improved anode design, the energy consumption of electrolyzed water is reduced, and the catalyst shows excellent catalytic activity in an acidic system.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of hydrogen production by electrolysis, and in particular to a preparation method and application of a carbon-based anode material. Background Art

[0002] Water electrolysis hydrogen production technology is a clean technology for producing high-purity hydrogen under mild conditions and is considered one of the most promising ways to produce hydrogen. However, the large-scale promotion of this technology is restricted by the high power consumption of hydrogen production. At present, the commercial water electrolysis hydrogen production system produces 1Nm 3 Hydrogen production usually consumes 4.5-5kWh of electricity, and its cost is 2-3 times that of fossil fuel hydrogen production. This is mainly because the anode oxygen evolution reaction (OER) has slow kinetics and high energy consumption, resulting in the electrolyzer chamber usually requiring a voltage of 1.6-2.0V to operate stably.

[0003] In order to reduce the power consumption of hydrogen production by electrolysis of water, researchers have proposed a new hydrogen production technology, carbon-assisted water electrolysis (CAWE), in recent years. By replacing the traditional anode OER with more easily oxidizable substances (such as coal, urea, etc.), the theoretical decomposition voltage of the anode reaction can be significantly reduced, thereby greatly reducing the power consumption of hydrogen production by electrolysis of water. Coal is configured into water-coal slurry for electrolysis because of its low price and wide source. Since 1979, the technology of hydrogen production by electrolysis of water-coal slurry has been a research hotspot for low-power hydrogen production technology. However, the coal-water system still faces a series of challenges. The solution resistance is large: the direct dissolution of coal in the aqueous solution will significantly increase the resistance of the solution, thereby reducing the electrochemical performance of the system. Uneven particle distribution: Coal powder is prone to sedimentation in the solution, resulting in uneven distribution of the active area of ​​the anode oxidation reaction, and it is very easy to cause pipeline blockage problems. In response to these problems, Chen Cong and others from Zhejiang University pre-oxidized the carbon cloth substrate and combined it with high-temperature nitrogen doping to synthesize graphite nanomaterials (Chen Cong. Research on the reaction path and anodic oxidation mechanism of coal and wastewater-assisted water electrolysis for hydrogen production [D]. Zhejiang University, 2024.). However, the preparation process of the anode material is time-consuming and has certain technical complexity. In addition, Ying Zhi's team from Shanghai University of Technology used biochar treatment technology to prepare it into biochar slurry for use as an anode electrolyte for water electrolysis for hydrogen production (patent number: CN202010124699.8). Although this method significantly improves the catalytic activity of biochar, the high resistance problem of biochar slurry has not been effectively solved. Chinese patent 202211326102.3 proposes a method for hydrogen production by water electrolysis assisted by self-supporting carbon anodes, which improves the electrode preparation process and uses a sheeting method to prepare electrodes. However, this improvement does not have a significant effect on improving current density. Another Chinese patent 202210001131.6 proposes a two-step method for electrolyzing water-coal slurry to produce hydrogen. This method avoids the direct addition of coal particles during the electrolytic hydrogen production process by decoupling the coal's function of reducing Fe3+ into the hydrothermal system. However, this design requires two heating devices, which increases the complexity of the system.

[0004] In view of the preparation complexity and performance limitations of traditional carbon-based materials, the present invention achieves efficient preparation and performance optimization of carbon-based anode materials through innovative design. The preparation process of the present invention is simple, and the carbon-based anode used is low-cost; the ratio optimization of the anode material significantly improves the electrochemical performance; the iron-based cycle-assisted water electrolysis hydrogen production system constructed based on the carbon-based anode material significantly reduces the energy consumption of hydrogen production and has the potential for large-scale promotion and application. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a preparation method and application of a carbon-based anode material.

[0006] The present invention improves the utilization rate of coal powder and reduces the solution resistance at the same time. Specifically, the coal powder is pretreated and mixed with Nafion solution and ethanol to form a stable suspension, and then evenly dripped on a carbon cloth substrate to form an electrode. Compared with the traditional coal-water system, this method can achieve: evenly fix the carbon powder on the anode surface to avoid the problem of particle sedimentation; increase the specific surface area of ​​the anode and improve the interface catalytic performance; increase the bonding strength between the carbon powder and the electrode material, thereby reducing the influence of the solution resistance during the electrolysis process.

[0007] A method for preparing a carbon-based anode material is specifically completed by the following steps:

[0008] 1. Preparation of carbon powder materials:

[0009] The coal powder and potassium hydroxide are mixed evenly to obtain a mixed sample;

[0010] 2. High temperature activated carbon materials:

[0011] Under the protection of nitrogen gas atmosphere, the mixed sample is heated to 850°C to 950°C, and kept at 850°C to 950°C for a period of time to obtain a high-temperature activated carbon material;

[0012] 3. Cleaning and sieving:

[0013] The carbon material activated at high temperature is washed to neutrality, dried, and sieved to obtain sieved carbon powder;

[0014] 4. Preparation of suspension:

[0015] The screened carbon powder, 5% Nafion solution and anhydrous ethanol are mixed evenly, and then ultrasonically dispersed to obtain a suspension;

[0016] 5. Evenly apply the suspension on the hydrophilic carbon cloth in batches and dry it to obtain the carbon-based anode material.

[0017] A carbon-based anode material is used in an iron-based cycle-assisted water electrolysis hydrogen production system.

[0018] The present invention solves the problems of uneven distribution of coal powder and high solution resistance in the traditional coal-water system by optimizing the suspension ratio and preparation process, and achieves the following goals:

[0019] (1) Enhance material stability and uniformity: evenly fix the carbon powder on the anode surface to avoid sedimentation and improve the uniformity and specific surface area of ​​the electrode active area;

[0020] (2) Optimizing electrochemical performance: Combining iron-based cycles (Fe 2+ / Fe 3+ ) system, significantly reducing the anodic oxidation potential, improving oxidation kinetics, and increasing the efficiency of hydrogen production by water electrolysis;

[0021] (3) Reduce the energy consumption of hydrogen production: Through iron-based circulation assistance and improved anode design, the energy consumption of water electrolysis is reduced, enabling it to exhibit excellent catalytic activity in an acidic system. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 LSV curve of the carbon-based anode material prepared in Example 1-3 in an electrolyte containing iron ions;

[0023] Figure 2 LSV curves of the carbon-based anode materials prepared in Examples 4-6 in an electrolyte containing iron ions;

[0024] Figure 3 LSV curves of the carbon-based anode materials prepared in Examples 7-9 in an electrolyte containing iron ions;

[0025] Figure 4 LSV curves of different commercially available substrate materials in an electrolyte containing iron ions;

[0026] Figure 5 LSV curves of the carbon-based anode material prepared in Example 2 in different electrolytes;

[0027] Figure 6 LSV curves of the carbon-based anode materials prepared in Examples 2 and 10-12 in an electrolyte containing iron ions. DETAILED DESCRIPTION

[0028] Specific implementation method 1: This implementation method is a method for preparing a carbon-based anode material, which is specifically completed according to the following steps:

[0029] 1. Preparation of carbon powder materials:

[0030] The coal powder and potassium hydroxide are mixed evenly to obtain a mixed sample;

[0031] 2. High temperature activated carbon materials:

[0032] Under the protection of nitrogen gas atmosphere, the mixed sample is heated to 850°C to 950°C, and kept at 850°C to 950°C for a period of time to obtain a high-temperature activated carbon material;

[0033] 3. Cleaning and sieving:

[0034] The carbon material activated at high temperature is washed to neutrality, dried, and sieved to obtain sieved carbon powder;

[0035] 4. Preparation of suspension:

[0036] The screened carbon powder, 5% Nafion solution and anhydrous ethanol are mixed evenly, and then ultrasonically dispersed to obtain a suspension;

[0037] 5. Evenly apply the suspension on the hydrophilic carbon cloth in batches and dry it to obtain the carbon-based anode material.

[0038] Specific implementation method 2: The difference between this implementation method and specific implementation method 1 is that the coal powder described in step 1 needs to be pretreated. The process of the pretreatment is: crush the coal block in a crusher and then screen it to obtain coal powder with a particle size of 0.5 mm, and use hydrochloric acid and hydrofluoric acid to wash the screened coal powder 1 to 2 times respectively to obtain deashed coal powder, that is, the pretreatment is completed; the specific process of washing the screened coal powder once with hydrochloric acid is: immerse the screened coal powder in hydrochloric acid with a mass fraction of 10% to 15% for 30 minutes to 60 minutes, and then rinse it with deionized water until it is neutral; the specific process of washing the screened coal powder once with hydrofluoric acid is: immerse the coal powder washed with hydrochloric acid in hydrofluoric acid with a mass fraction of 5% to 10% for 30 minutes to 60 minutes, and then rinse it with deionized water until it is neutral; the mass ratio of coal powder to potassium hydroxide described in step 1 is 1: (2 to 4). The other steps are the same as those in specific implementation method 1.

[0039] Specific implementation method three: The difference between this implementation method and specific implementation methods one or two is that the heating rate described in step two is 5°C / min to 10°C / min; the insulation time described in step two is 3h to 6h.

[0040] The other steps are the same as those in the first or second embodiment.

[0041] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that: in step 3, the carbon material activated at high temperature is washed to neutrality with deionized water, then dried, and filtered through 60-80 meshes to obtain screened carbon powder. The other steps are the same as those of specific embodiments 1 to 3.

[0042] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that the mass volume ratio of the carbon powder, 5% Nafion solution and anhydrous ethanol in step 4 is 5 mg: (20 μL-40 μL): (460 μL-480 μL); the ultrasonic dispersion time in step 4 is 1 h-2 h. The other steps are the same as those in specific embodiments 1 to 4.

[0043] Specific embodiment 6: The difference between this embodiment and specific embodiments 1 to 5 is that the size of the carbon cloth in step 5 is 1 cm×1 cm; the drying temperature in step 5 is 70° C. to 90° C.;

[0044] In step 5, after each drop of the suspension, it needs to be dried before the next drop, and 50 μL of the suspension is dropped each time; the mass of the suspension in step 5 and the surface area of ​​the hydrophilic carbon cloth are 500 μL:1 cm 2 The other steps are the same as those in Specific Embodiments 1 to 5.

[0045] Specific implementation method seven: This implementation method is the application of a carbon-based anode material in an iron-based cycle-assisted water electrolysis hydrogen production system.

[0046] Specific embodiment eight: This embodiment differs from specific embodiments one to seven in that the carbon-based anode material is used in an iron-based cycle-assisted water electrolysis hydrogen production system, which is specifically completed in the following steps: using the carbon-based anode material as a working electrode, using an electrode that can undergo a hydrogen evolution reaction as a counter electrode, and using a mercurous sulfate electrode as a reference electrode; placing the working electrode, the counter electrode, and the reference electrode in an electrolytic cell, then adding an electrolyte containing iron ions to the electrolytic cell, assembling a water electrolysis hydrogen production device, connecting a power supply, and conducting a three-electrode system water electrolysis hydrogen production test at a fixed electrolysis temperature. The other steps are the same as those of specific embodiments one to seven.

[0047] Specific embodiment 9: This embodiment differs from specific embodiments 1 to 8 in that: the electrode capable of undergoing hydrogen evolution reaction is a Pt mesh, a Pt sheet, a Ni electrode, a carbon cloth or a graphite felt; the electrolyte containing iron ions is a mixture of sulfuric acid, ferrous sulfate and water, wherein the concentration of sulfuric acid is 1 mol / L, and the concentration of ferrous sulfate is 1 mol / L. The other steps are the same as those of specific embodiments 1 to 8.

[0048] Specific embodiment 10: This embodiment differs from specific embodiments 1 to 9 in that the electrolyte temperature is 60° C. The other steps are the same as those of specific embodiments 1 to 9.

[0049] The following examples are used to verify the beneficial effects of the present invention:

[0050] Example 1: A method for preparing a carbon-based anode material, which is specifically completed by the following steps:

[0051] 1. Preparation of carbon powder materials:

[0052] The coal block is crushed in a crusher and then sieved to obtain coal powder with a particle size of 0.5 mm, and the sieved coal powder is washed twice with hydrochloric acid and hydrofluoric acid respectively to obtain deashed coal powder; the deashed coal powder is evenly mixed with potassium hydroxide to obtain a mixed sample;

[0053] The mass ratio of the deashed coal powder to potassium hydroxide in step 1 is 1:2;

[0054] The specific process of using hydrochloric acid to wash the sieved coal powder once in step 1 is as follows: immerse the sieved coal powder in 15% hydrochloric acid by mass for 30 minutes, and then rinse with deionized water until it is neutral;

[0055] The specific process of using hydrofluoric acid to wash the screened coal powder once in step 1 is as follows: immerse the coal powder washed with hydrofluoric acid in 10% hydrofluoric acid by mass for 30 minutes, and then rinse with deionized water until it is neutral;

[0056] 2. High temperature activated carbon materials:

[0057] Under the protection of nitrogen gas atmosphere, the mixed sample was heated to 900°C at a heating rate of 5°C / min and kept at 900°C for 6 hours to obtain a high-temperature activated carbon material;

[0058] 3. Cleaning and sieving:

[0059] The carbon material activated at high temperature is washed with deionized water until it is neutral, then dried, and passed through 60-80 meshes to obtain screened carbon powder;

[0060] 4. Preparation of suspension:

[0061] The screened carbon powder, 5% Nafion solution and anhydrous ethanol were mixed evenly, and then ultrasonically dispersed for 1 hour to obtain a suspension;

[0062] The mass volume ratio of the carbon powder, 5% Nafion solution and anhydrous ethanol described in step 4 is 5 mg: 20 μL: 480 μL;

[0063] 5. The suspension obtained in step 4 was evenly applied on a hydrophilic carbon cloth (commercially available) with a size of 1 cm×1 cm in batches, and dried at 80° C. to obtain a carbon-based anode material (denoted as A-1);

[0064] In step 5, each time the suspension is dripped, it needs to be dried before the next dripping. 50 μL of the suspension is dripped each time.

[0065] Example 2: The difference between this example and Example 1 is that the mass volume ratio of the carbon powder, 5% Nafion solution and anhydrous ethanol described in step 4 is 5 mg: 30 μL: 470 μL; the carbon-based anode material (denoted as A-2 or A-2-hydrophilic carbon cloth) obtained in step 5. The other steps and parameters are the same as those in Example 1.

[0066] Example 3: The difference between this example and Example 1 is that the mass volume ratio of the carbon powder, 5% Nafion solution and anhydrous ethanol in step 4 is 5 mg:40 μL:460 μL; the carbon-based anode material (denoted as A-3) obtained in step 5. The other steps and parameters are the same as those in Example 1.

[0067] Example 4: This example differs from Example 1 in that the mass ratio of the deashed coal powder to potassium hydroxide in step 1 is 1:3; the carbon-based anode material (denoted as B-1) obtained in step 5. The other steps and parameters are the same as those in Example 1.

[0068] Example 5: The difference between this example and Example 1 is that the mass ratio of the deashed coal powder to potassium hydroxide in step 1 is 1:3; the mass volume ratio of the carbon powder, 5% Nafion solution and anhydrous ethanol in step 4 is 5 mg: 30 μL: 470 μL; the carbon-based anode material (denoted as B-2) obtained in step 5. The other steps and parameters are the same as those in Example 1.

[0069] Example 6: The difference between this example and Example 1 is that the mass ratio of the deashed coal powder to potassium hydroxide in step 1 is 1:3; the mass volume ratio of the carbon powder, 5% Nafion solution and anhydrous ethanol in step 4 is 5 mg: 40 μL: 460 μL; the carbon-based anode material (denoted as B-3) obtained in step 5. The other steps and parameters are the same as those in Example 1.

[0070] Example 7: This example differs from Example 1 in that the mass ratio of the deashed coal powder to potassium hydroxide in step 1 is 1:4; the carbon-based anode material (denoted as C-1) obtained in step 5. The other steps and parameters are the same as those in Example 1.

[0071] Example 8: The difference between this example and Example 1 is that the mass ratio of the deashed coal powder to potassium hydroxide in step 1 is 1:4; the mass volume ratio of the carbon powder, 5% Nafion solution and anhydrous ethanol in step 4 is 5 mg: 30 μL: 470 μL; the carbon-based anode material (denoted as C-2) obtained in step 5. The other steps and parameters are the same as those in Example 1.

[0072] Example 9: The difference between this example and Example 1 is that the mass ratio of the deashed coal powder to potassium hydroxide in step 1 is 1:4; the mass volume ratio of the carbon powder, 5% Nafion solution and anhydrous ethanol in step 4 is 5 mg: 40 μL: 460 μL; the carbon-based anode material (denoted as C-3) obtained in step 5. The other steps and parameters are the same as those in Example 1.

[0073] Example 10: The difference between this example and Example 1 is that in step 5, the hydrophilic carbon cloth with a size of 1 cm×1 cm is replaced with carbon felt with a size of 1 cm×1 cm; the carbon-based anode material obtained in step 5 (referred to as A-2-carbon felt). The other steps and parameters are the same as those in Example 1.

[0074] Example 11: The difference between this example and Example 1 is that in step 5, the hydrophilic carbon cloth with a size of 1 cm×1 cm is replaced with a graphite felt with a size of 1 cm×1 cm; the carbon-based anode material obtained in step 5 (denoted as A-2-graphite felt). The other steps and parameters are the same as those in Example 1.

[0075] Example 12: The difference between this example and Example 1 is that in step 5, the hydrophilic carbon cloth with a size of 1 cm×1 cm is replaced with carbon paper with a size of 1 cm×1 cm; the carbon-based anode material obtained in step 5 (referred to as A-2-carbon paper). The other steps and parameters are the same as those in Example 1.

[0076] In order to better illustrate the application effect of the carbon-based electrode prepared in the present invention in the iron-based cycle-assisted water electrolysis to produce hydrogen, the polarization curve of the working electrode was recorded by a BioLogic-VMP3 electrochemical workstation.

[0077] LSV curves of carbon-based anode materials prepared with different amounts of nafion in 80 mL of electrolyte containing iron ions (the electrolyte containing iron ions is a mixture of sulfuric acid, ferrous sulfate and water, wherein the concentration of sulfuric acid is 1 mol / L and the concentration of ferrous sulfate is 1 mol / L). The test was carried out in an acidic system, using an H-type electrolytic cell, nafion117 as the diaphragm, and a three-electrode system at an operating temperature of 60°C. The working electrodes were the carbon-based anode materials obtained in Examples 1 to 3, the counter electrode was a 1 cm×1 cm platinum sheet electrode, and the reference electrode was a mercurous sulfate electrode, see Figure 1 As shown;

[0078] Figure 1 LSV curve of the carbon-based anode material prepared in Example 1-3 in an electrolyte containing iron ions;

[0079] from Figure 1 It can be seen that the activity order of carbon-based anodes is: A-2>A-3>A-1.

[0080] LSV curves of carbon-based anode materials prepared with different amounts of nafion in 80 mL of electrolyte containing iron ions (the electrolyte containing iron ions is a mixture of sulfuric acid, ferrous sulfate and water, wherein the concentration of sulfuric acid is 1 mol / L and the concentration of ferrous sulfate is 1 mol / L). The test was carried out in an acidic system, using an H-type electrolytic cell, nafion117 as the diaphragm, and a three-electrode system at an operating temperature of 60°C. The working electrodes were the carbon-based anode materials obtained in Examples 4 to 6, the counter electrode was a 1 cm×1 cm platinum sheet electrode, and the reference electrode was a mercurous sulfate electrode, see Figure 2 As shown;

[0081] Figure 2LSV curves of the carbon-based anode materials prepared in Examples 4-6 in an electrolyte containing iron ions;

[0082] from Figure 2 It can be seen that the activity order of carbon-based anodes is: B-3>B-1>B-2.

[0083] LSV curves of carbon-based anode materials prepared with different amounts of nafion in 80 mL of electrolyte containing iron ions (the electrolyte containing iron ions is a mixture of sulfuric acid, ferrous sulfate and water, wherein the concentration of sulfuric acid is 1 mol / L and the concentration of ferrous sulfate is 1 mol / L). The test was carried out in an acidic system, using an H-type electrolytic cell, nafion117 as the diaphragm, and a three-electrode system at an operating temperature of 60°C. The working electrodes were the carbon-based anode materials obtained in Examples 7 to 9, the counter electrode was a 1 cm×1 cm platinum sheet electrode, and the reference electrode was a mercurous sulfate electrode, see Figure 3 As shown;

[0084] Figure 3 LSV curves of the carbon-based anode materials prepared in Examples 7-9 in an electrolyte containing iron ions;

[0085] from Figure 3 It can be seen that the activity order of carbon-based anodes is: C-3>C-2>C-1.

[0086] LSV curve of commercially available electrode substrate in 80mL electrolyte containing iron ions (the electrolyte containing iron ions is a mixture of sulfuric acid, ferrous sulfate and water, wherein the concentration of sulfuric acid is 1mol / L and the concentration of ferrous sulfate is 1mol / L). The test was carried out in an acidic system, using an H-type electrolytic cell, a diaphragm of nafion117, a three-electrode system, and an operating temperature of 60°C. The working electrodes were hydrophilic carbon cloth, graphite felt, carbon felt, and carbon paper, the counter electrode was a 1cm×1cm platinum sheet electrode, and the reference electrode was a mercurous sulfate electrode, see Figure 4 As shown;

[0087] Figure 4 LSV curves of different commercially available substrate materials in an electrolyte containing iron ions;

[0088] from Figure 4 It can be seen that the activity order of carbon-based anodes is: hydrophilic carbon > carbon felt > graphite felt > carbon paper.

[0089] Comparative Examples 1 to 9, the carbon-based anode material with the best performance was selected as A-2, and A-2 was taken as the working electrode for testing. Figure 5The LSV curves of Example 2 in different electrolytes are shown in Figure 2. The test was conducted in an acidic system, using an H-type electrolytic cell, a diaphragm of nafion117, a three-electrode system, and an operating temperature of 60°C. The working electrode is Example 2, the counter electrode is a 1cm×1cm platinum sheet electrode, and the reference electrode is a mercurous sulfate electrode. 80mL of the three electrode solutions were added to the cathode and anode, respectively. Figure 5 As shown;

[0090] Electrolyte I: 1 mol / L sulfuric acid solution (denoted as 1M H2SO4);

[0091] Electrolyte II: a mixture of sulfuric acid, ferrous sulfate and water, wherein the concentration of sulfuric acid is 1 mol / L and the concentration of ferrous sulfate is 0.05 mol / L (recorded as 1M H2SO4+0.05M FeSO4);

[0092] Electrolyte III: a mixture of sulfuric acid, ferrous sulfate and water, wherein the concentration of sulfuric acid is 1 mol / L and the concentration of ferrous sulfate is 0.1 mol / L (recorded as 1M H2SO4+0.10M FeSO4);

[0093] Figure 5 LSV curves of the carbon-based anode material prepared in Example 2 in different electrolytes;

[0094] from Figure 5 It can be seen that the carbon-based anode material prepared in Example 2 exhibits good activity in a mixed solution of 1 mol / L sulfuric acid solution and 0.10 mol / L ferrous sulfate.

[0095] LSV curves of the carbon-based anode materials prepared in Example 2 and Example 10-12 in an electrolyte (a mixture of sulfuric acid, ferrous sulfate and water, wherein the concentration of sulfuric acid is 1 mol / L and the concentration of ferrous sulfate is 0.1 mol / L). The test was carried out in an acidic system, using an H-type electrolytic cell, a diaphragm of nafion117, a three-electrode system, and an operating temperature of 60°C. The working electrodes were Example 2 and Example 10-12, the counter electrode was a 1 cm×1 cm platinum sheet electrode, and the reference electrode was a mercurous sulfate electrode. 80 mL of electrolyte was added to the cathode and anode, respectively, and the electrolyte was added to the cathode and anode, respectively. Figure 6 shown.

[0096] Figure 6 LSV curves of the carbon-based anode materials prepared in Example 2 and Examples 10-12 in an electrolyte containing iron ions;

[0097] from Figure 6 It can be seen that the activity order of carbon-based anodes is: A-2-graphite felt>A-2-carbon felt>A-2-hydrophilic carbon cloth>A-2-carbon paper.

Claims

1. A method for preparing a carbon-based anode material, characterized in that The preparation method is specifically completed according to the following steps:

1. Preparation of carbon powder materials: The coal powder and potassium hydroxide are mixed evenly to obtain a mixed sample; 2. High temperature activated carbon materials: Under the protection of nitrogen gas atmosphere, the mixed sample is heated to 850°C to 950°C, and kept at 850°C to 950°C for a period of time to obtain a high-temperature activated carbon material; 3. Cleaning and sieving: The carbon material activated at high temperature is washed to neutrality, dried, and sieved to obtain sieved carbon powder; 4. Preparation of suspension: The screened carbon powder, 5% Nafion solution and anhydrous ethanol are mixed evenly, and then ultrasonically dispersed to obtain a suspension; 5. Evenly apply the suspension on the hydrophilic carbon cloth in batches and dry it to obtain the carbon-based anode material.

2. The method for preparing a carbon-based anode material according to claim 1, characterized in that The coal powder described in step one needs to be pretreated, and the pretreatment process is as follows: the coal block is crushed in a crusher and then screened to obtain coal powder with a particle size of 0.5 mm, and the screened coal powder is washed 1 to 2 times with hydrochloric acid and hydrofluoric acid respectively to obtain deashed coal powder, that is, the pretreatment is completed; the specific process of washing the screened coal powder once with hydrochloric acid is as follows: immersing the screened coal powder in hydrochloric acid with a mass fraction of 10% to 15% for 30 minutes to 60 minutes, and then rinsing it with deionized water until it is neutral; the specific process of washing the screened coal powder once with hydrofluoric acid is as follows: immersing the coal powder washed with hydrochloric acid in hydrofluoric acid with a mass fraction of 5% to 10% for 30 minutes to 60 minutes, and then rinsing it with deionized water until it is neutral; the mass ratio of the coal powder to potassium hydroxide described in step one is 1: (2 to 4).

3. The method for preparing a carbon-based anode material according to claim 1, characterized in that The heating rate in step 2 is 5°C / min to 10°C / min; the insulation time in step 2 is 3h to 6h.

4. The method for preparing a carbon-based anode material according to claim 1, characterized in that In step 3, the carbon material activated at high temperature is washed with deionized water until it is neutral, and then dried and filtered through 60-80 meshes to obtain screened carbon powder.

5. The method for preparing a carbon-based anode material according to claim 1, characterized in that The mass volume ratio of the carbon powder, 5% Nafion solution and anhydrous ethanol described in step 4 is 5 mg: (20 μL-40 μL): (460 μL-480 μL); the time of ultrasonic dispersion described in step 4 is 1 h-2 h.

6. The method for preparing a carbon-based anode material according to claim 1, characterized in that The size of the carbon cloth in step 5 is 1 cm×1 cm; the drying temperature in step 5 is 70° C. to 90° C.; In step 5, after each drop of the suspension, it needs to be dried before the next drop, and 50 μL of the suspension is dropped each time; the mass of the suspension in step 5 and the surface area of ​​the hydrophilic carbon cloth are 500 μL:1 cm 2 .

7. Use of a carbon-based anode material prepared by the preparation method according to claim 1, characterized in that A carbon-based anode material is used in an iron-based cycle-assisted water electrolysis hydrogen production system.

8. The use of a carbon-based anode material according to claim 7, characterized in that The carbon-based anode material is used in an iron-based cycle-assisted water electrolysis hydrogen production system, which is specifically completed in the following steps: using the carbon-based anode material as a working electrode, using an electrode that can undergo a hydrogen evolution reaction as a counter electrode, and using a mercurous sulfate electrode as a reference electrode; placing the working electrode, the counter electrode and the reference electrode in an electrolytic cell, then adding an electrolyte containing iron ions into the electrolytic cell, assembling a water electrolysis hydrogen production device, connecting a power supply, and conducting a three-electrode system water electrolysis hydrogen production test at a fixed electrolysis temperature.

9. The use of a carbon-based anode material according to claim 8, characterized in that The electrode capable of generating hydrogen evolution reaction is a Pt mesh, a Pt sheet, a Ni electrode, a carbon cloth or a graphite felt; the electrolyte containing iron ions is a mixture of sulfuric acid, ferrous sulfate and water, wherein the concentration of sulfuric acid is 1 mol / L, and the concentration of ferrous sulfate is 1 mol / L.

10. The use of a carbon-based anode material according to claim 8, characterized in that The electrolyte temperature is 60°C.

Citation Information

Patent Citations

  • Biochar electrochemical reforming hydrogen production method based on biomass multistage utilization

    CN111206256A

  • Method for producing hydrogen by electrolyzing coal water slurry through two-step method

    CN114134511A

  • A method for producing hydrogen by electrolysis of water using a self-supporting carbon anode

    CN115466969B